التحاكم الدولي كبديل مؤقت للتحاكم العربي في تسوية المنازعـــــات الحدودية والإقليمية - كوسة, عمار (revue mofakir; No 12 (2015): مجلـــة المفكــر, 2018)
Arab countries have inherited some territorial and frontiers' disputes right after decolonisation or their independence. These conflicts affected badly their political, economic & social relations and even menaced their peace and security.The political settlement couldn't succeed in solving the problem so it was necessary to turn to international adjudication which was a success in the few submitted cases, particularly with the absence of the system within the Arab world.The main problematic of our research is to find out the reasons behind this success. Was the absence of Arab adjudication system the right reason? and if so, why Arab countries haven't created it?, Is this international adjudication system the only settling Arab territorial and frontiers conflicts means awaiting the creation of a proper Arab one?We concluded that Arab adjudication system is necessary (at least an international Arab Court) for the settlement of their disputes including numerous territorial and frontiers' disputes waiting for solution. The creation of such a system will help the Arab league to find solutions for all legal problems arising within it and avoiding the use of the international political and adjudication system. While waiting for the creation of such a system within the Arab World, all Arab disputes are to be treated solely by the international adjudication system.